Eletrocoagulação como pré-tratamento de efluente de indústria de palmito em conserva - Jesus, Bruna Meira de (2020)
The concern of industry managers is increasing with the establishment of more efficient production processes, with lower input costs and water consumption. The scientific community plays an important role in this problem as it seeks to develop solutions that meet environmental requirements at viable costs. The present study evaluated the use of electrocoagulation as a pre-treatment for effluents from a canned palm heart industry located in Antonina/PR, with the objective of evaluating the efficiency of electrocoagulation as a pretreatment of effluent from a canned heart of palm production industry. Electrocoagulation tests were performed with synthetic effluent, simulating the same composition of the substances added in the palm heart preservation brine formulation used by the industry that supplied the raw effluent, comprising 35 g.L-1 salt (NaCl), 8 ,5 g citric acid (C6H8O7) e real efluent. Aluminum and iron electrodes, current of 1,5, 1,0 and 0,7 A, distance between electrodes of 2 and 3 cm were used in 30 minute tests. In a second step, the combined treatment of electrocoagulation aided with an organic flocculating agent, Tanfloc SG, at concentrations 100, 125 and 150 mg.L-1 was evaluated. The best treatment configuration obtained for both the synthetic effluent and the actual effluent was with iron electrodes at 2 cm distance and combined treatment with the flocculating agent, using a concentration of 100 mg.L-1 of Tanfloc SG. The synthetic effluent resulted in 39 mg.L-1 (90,3% removal) of COD, 11,4 NTU of turbidity and 15,6 mg.L-1 of residual iron. The real effluent resulted in 276 mg.L-1 (70,3% removal) of COD, 13,3 NTU of turbidity and 21,4 mg.L-1 of residual iron. It is concluded that the electrocoagulation treatment system is suitable for the study effluent.